Gobiidae Fish Species Diversity in the Hoi Estuary of the Ma River, Thanh Hoa Province, Vietnam - Thao, Hoang Ngoc; Thu, Trinh Thi; Nam, Nguyen Thanh; Tuan, Ho Anh (Innovations in Biological Science Vol. 3, 2024)
Fieldwork in the Hoi estuary area of the Ma River has collected 33 specimens in 2021 and 2022, and nine species of Gobiidae have been recorded. Three of these species are recorded for the first time in the study area, including Acentrogobius caninus (Valenciennes, 1837), Glossogobius olivaceus (Temminck & Schlegel, 1845), and Oxyurichthys papuensis (Valenciennes, 1837). This paper provides morphological characteristics of nine species collected in the study area, also update the list of Gobiid species in the Hoi estuary; it now includes 18 species, accounts for 11.61% of the total number of Gobies species currently known in Vietnam. This proves the diversity of fish species in the study area. This result contributes to the understanding of the Gobiid group as well as the fish fauna in the study area.